Profilin-1 mutations are rare in patients with amyotrophic lateral sclerosis and frontotemporal dementia. Issue 5 (September 2013) - van Blitterswijk, Marka; Baker, Matthew C.; Bieniek, Kevin F.; Knopman, David S.; Josephs, Keith A.; Boeve, Bradley; Caselli, Richard; Wszolek, Zbigniew K.; Petersen, Ronald; Graff-Radford, Neill R.; Boylan, Kevin B.; Dickson, Dennis W.; et al.
Abstract: Mutations in profilin-1 ( PFN1 ) have recently been identified in patients with amyotrophic lateral sclerosis (ALS). Because of the considerable overlap between ALS and the common subtype of frontotemporal dementia, which is characterized by transactive response DNA-binding protein 43 pathology (FTLD-TDP), we tested cohorts of ALS and FTLD-TDP patients for PFN1 mutations. DNA was obtained from 342 ALS patients and 141 FTLD-TDP patients at our outpatient clinic and brain bank for neurodegenerative diseases at the Mayo Clinic Florida, Jacksonville, USA. We screened these patients for mutations in coding regions of PFN1 by Sanger sequencing. Subsequently, we used TaqMan genotyping assays to investigate the identified variant in 1167 control subjects. From the results, one variant, p.E117G, was detected in one ALS patient, one FTLD-TDP patient, and two control subjects. The mutation frequency of patients versus control subjects was not significantly different ( p -value = 0.36). Moreover, PFN1 and TDP-43 staining of autopsy material did not differ between patients with or without this variant. In conclusion, the p.E117G variant appears to represent a benign polymorphism. PFN1 mutations, in general, are rare in ALS and FTLD-TDP patients.